Oncological outcomes of neoadjuvant chemotherapy in patients with resectable synchronous colorectal liver metastasis: A result from a propensity score matching study - Jiang, Yu-Juan; Zhou, Si-Cheng; Chen, Jing-Hua; Liang, Jian-Wei (Frontiers in Oncology, 2022)
Background The efficacy and safety of neoadjuvant chemotherapy (NAC) in treating resectable synchronous colorectal liver metastases (CRLM) remain controversial. Methods Data from CRLM patients who underwent simultaneous liver resection between January 2015 and December 2019 were collected from the SEER database (SEER cohort) and a single Chinese Cancer Center (NCC cohort). Using a 1:2 ratio of PSM analysis, the prognostic impact of NAC between patients who underwent NAC before surgical treatment and patients who underwent surgical treatment alone was evaluated. Results After PSM, there was no significant difference in overall survival (OS) for those given NAC prior to resection of CRLM compared with surgery alone for the NCC cohort and SEER cohort (each P > 0.05). Age was an independent predictor of OS only in the SEER cohort (P = 0.040), while the pN stage was an independent predictor for OS only in the NCC center (P = 0.002). In addition, DFS was comparable among the two groups in the NCC cohort; multivariable Cox proportional hazard regression showed that pN stage, size of primary disease, and histologic grade were associated with poor DFS (each P < 0.05). In a subgroup analysis, the DFS and OS in the NAC- group were significantly worse than those in the NAC+ group for patients with more than two liver metastases (each P < 0.05). Conclusion NAC did not show a significant prognostic impact in the entire cohort of patients with resectable synchronous CRLM. However, patients with more than two liver metastases could be good candidates for indication of NAC.